Electrically heated carbon textile reinforced concrete – perspectives for multifaceted building concepts - Dahlhoff Annette; Raupach Michael (MATEC Web of Conferences)
Carbon textile reinforced concrete (CTRC) is currently used as a high-performance composite material in the construction industry, comprising concrete and a non-metallic reinforcement. In addition to remarkable material properties such as tensile load-bearing behaviour, durability and density, this innovative material features high electrical conductivity, offering the potential for electrical heat generation within building components. In this context, the electrical conductivity of carbon fibres, as well as their high thermal conductivity along the fibre direction can be utilized for accelerating processes such as the hydration of concrete in the composite material or the development of electrically heated carbon textile reinforced concrete. For this purpose, investigations have been carried out on material combinations with textile reinforcement (CTR) and ultra-high-performance concrete, with a specific focus on the electrically heated carbon textile reinforcements at temperatures up to 80 °C. The impact of electrical heating of CTR was evaluated by analyzing the specific resistance on selected non-metallic reinforcement materials. For the composite material (CTRC) tensile strength tests and heating tests were performed. To facilitate the evaluation of the CTRC, an automated crack evaluation software was developed and validated for the results from laboratory tests utilizing digital image correlation. This software automatically determines the crack behaviour such as crack widths and stress-strain behaviour for the users in the form of a graphical user interface. This interdisciplinary approach connects materials science with thermal management in concrete construction, providing valuable insights into the practical use of CTR in multifaceted building concepts.